The Effect of Mineralizers on Synthesis of Er2Ce2O7 - Hablovičová, Blanka; Šulcová, Petra (Česká společnost průmyslové chemie, 2016)
Pigment with pyrochlore structure Er2Ce2O7 was prepared by mechanical activation. Mineralizers CaCl2, Na2B4O7, FeCl3-NaCl, CeCl3-KCl and MgCl2-MgO were added in 5 wt. % before firing at temperature 1400 °C for 3 hours (heating rate 10 °C·min-1) in the electric furnace. Colour properties in the organic matrix in mass tone and ceramic glaze G 070 91 in 10 wt. %, particle size distribution and phase composition were investigated. Synthetized samples were visually pink or brown-orange in organic matrix and orange in the ceramic glaze. Er2Ce2O7 was always created but samples were not single-phase mostly.
Efekt mineralizátorů na syntézu Er2Ce2O7
Keywords: Mineralizers; Mechanical Activation; Lanthanides; Mineralizátory; mechanická aktivace; lanthanoidy